Factors Affecting Company Value in Manufacturing Companies in the Agricultural Subsector Listed on the Indonesian Stock Exchange - Mursalini, Wahyu Indah; Yeni, Afni; Iswara, Nada (CV. Proaksara Global Transeduka, 2026)
This investigation aims to unravel the antecedents that shape Firm Value within Manufacturing Corporations in the Plantation Sub-sector listed on the Indonesia Stock Exchange. The study encompassed 15 entities selected through purposive sampling over the period from 2019 to 2023. By employing multiple linear regression, it was inferred that the Current Ratio and Debt to Equity Ratio exhibit a discernible influence on Firm Value, as articulated in the regression equation: Y = 0.341 + 0.186X1 + 0.369X2 + e. The results of the t-test indicated that the Current Ratio (X1) does not have a significant effect on Firm Value, with a t-value of 1.365 < t-table 1.993 and a significance value of 0.179 > 0.05. Therefore, the first hypothesis is rejected. Conversely, the Debt to Equity Ratio (X2) has a significant effect on Firm Value, with a t-value of 3.339 > t-table 1.993 and a significance value of 0.002 < 0.05. Thus, the second hypothesis is accepted. Furthermore, the F-test results showed that both the Current Ratio and Debt to Equity Ratio simultaneously have a significant effect on Firm Value, with a F-value of 6.448 > F-table 3.124 and a significance value of 0.003 < 0.05. Therefore, the third hypothesis is accepted. The coefficient of determination test produced an R-squared value of 0.223. This means that the independent variables, Current Ratio and Debt to Equity Ratio, explain 22.3% of the variation in Firm Value, while the remaining 77.7% is explained by other factors outside this research model.